The age o Carrion (1859-1885). - Cabieses, Fernando (2015)
During the last 110 years, the Peruvian doctors have heard repeated the story of who scored, with the sacrifice of his life, delivery guidelines provide guidance to all generations of dedicated men and women; the health of our fellow human beings. Again telling the biography of Daniel Alcides Carrión and review in detail the events that led to his magnanimous gesture must be redundant and unnecessary for many others. But we must pay tribute to the 110 years.